Regulation of intracellular calcium signaling, localized signals and oscillations - Ehrlich, Barbara (Henry Stewart Talks, 2007)
Calcium as a trigger for many cellular events including muscle contraction, hormone secretion and cell growth, The release of calcium from intracellular stores using electrophysiological, biochemical and molecular techniques combined with imaging, Regulation by chromogranin, a protein that binds to the major calcium release channel, the InsP3R, Regulation by a steroid hormone both at physiological and supra-physiological levels, Regulation by a protein tyrosine phosphatase SHP-2, The consequences of mutations or non-physiological modulations of each pathway